Surrogate Ethnography: Fieldwork, the Academy, and Resisting the IRB. (February 2018) - Newmahr, Staci; Hannem, Stacey
Nearly every ethnographer has observed the growing reach and increasingly uncomfortable power of the IRB. As IRB restrictions have grown tighter, the consequences have become more dire. The failure of most IRBs to understand ethnography at all, along with increasing concerns about litigation that trump the welfare of both researchers and "subjects, " and the usurping of faculty power by the administration in universities, has left us with a difficult challenge: how can ethnographers and participant observers continue to do their research, without losing their jobs? This paper introduces a new methodology ("surrogate ethnography"). We posit that surrogate ethnography provides three distinct benefits: (1) it represents a methodological and ethical resistance to excessive IRB control, (2) it can help us rescue ethnography and participant observation—at least in a certain form—from IRBs, and (3) it addresses some of the longstanding concerns with autoethnography by proposing an alternative reflective analytic approach to one's experiences in the field. We share the results of our initial foray into surrogate ethnography, offering our analyses of each other's stories (one from volunteer work in a prison, and one from participation in sadomasochism/BDSM) in the context of constraints and challenges facing ethnographers in the current academic climate.